A case of delayed initial response to combination ipilimumab and nivolumab in malignant pleural mesothelioma - Hewa, Chamodi Pillippu; Khan, Yasir (Trends in Immunotherapy, 2024)
Malignant pleural mesothelioma has a poor prognosis with limited therapeutic options Although numerous trials have shown that combination immunotherapy with nivolumab and ipilimumab is one of the first line treatments for patients with unresectable MPM, there is limited data on delayed responses over a long follow up period. We report a case of a delayed response 7 months after the cessation of immunotherapy in a patient who initially had progressive malignant pleural mesothelioma with metastases.